Openness as strength: The win-win in EU-US digital services trade - Matthias Bauer; Dyuti Pandya; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
The discourse surrounding the EU's supposed over-reliance on digital services imports from non-EU countries, particularly the US, has been a recurrent topic among some political circles. However, this viewpoint tends to oversimplify and misrepresent the nuanced and complex reality of the EU's status within the global Information and Communication Technology (ICT) sector and digitally enabled trade. A thorough analysis of trade data and trends clearly illustrates that the EU's engagement with foreign (non-EU) digital services, notably from the US, represents a strategic economic advantage, bolstering Europe's competitiveness and fostering productivity growth. Below we underline the critical importance of openness to foreign innovation and technology diffusion for the EU's economic future.
Keywords: 330